2018
DOI: 10.3399/bjgp18x695789
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction tool for patients presenting with acute cough in primary care: a prognostic study spanning six European countries

Abstract: The new prediction rule outperforms all existing alternatives in predicting poor outcome in adult patients presenting to primary care with acute cough and could not be improved by including additional test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…We found no death, a low rate of hospital admissions, an improvement in half of patients after three days and complete recovery in 79% of patients after one month. A benign course of acute cough was also found by Bruyndonckx et al [ 71 ]. A systematic review assessing primary, secondary, and tertiary care found a weighted mean duration of any cough of 17.8 days (range 15.3 to 28.6 days) and 13.9 days for productive cough (range 13.3 to 17.4 days) [ 75 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We found no death, a low rate of hospital admissions, an improvement in half of patients after three days and complete recovery in 79% of patients after one month. A benign course of acute cough was also found by Bruyndonckx et al [ 71 ]. A systematic review assessing primary, secondary, and tertiary care found a weighted mean duration of any cough of 17.8 days (range 15.3 to 28.6 days) and 13.9 days for productive cough (range 13.3 to 17.4 days) [ 75 ].…”
Section: Discussionsupporting
confidence: 69%
“…Accurate prediction of the course of cough could decrease antibiotic overprescribing [ 71 , 72 ]. Half of antibiotic prescriptions for acute respiratory conditions in US ambulatory care visits seem to be unnecessary [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study on the aetiology, diagnosis and prognosis, and a nested RCT on the effect of amoxicillin in adult acute cough patients were conducted between November 2007 and April 2010 within the GRACE Network of Excellence [3,7,9,12]. Patients originated from 16 primary care networks within 12 European countries (Belgium, England, France, Germany, Italy, the Netherlands, Poland, Spain, Slovakia, Slovenia, Sweden and Wales).…”
Section: Datamentioning
confidence: 99%
“…This study used data from 2604 patients who presented with an acute cough in primary care to develop an algorithm to predict poor outcomes 1. Poor outcome was defined as a reconsultation with new or worsened symptoms, or hospital admission.…”
Section: Overviewmentioning
confidence: 99%